What's the Big Deal About Big Data Loss (Actually Theft)?. Issue 6 (3rd June 2017) - Cohen, Fred
Abstract: I get confused about the way security deals with so-called data loss (actually theft). Recently we had what the media called, in various forms, a crisis, a huge cyberattack against, and so forth against JPMorgan Chase (JP), one of many such instances in the last year. So I looked at the various claims surrounding this instance, and found consistently that the only known "loss" of data was names, addresses, phone numbers, and e-mail addresses. And it was not lost! It was stolen, and JP still has copies. So, to be really clear, this is more or less the same information found in the phone book, available from various mailing list providers for less than a tenth of a penny a piece, and of no significant consequence I can identify. The cost of "protection" for consumers is $90 per person per year, although I do not quite get what this cost covers.